Cutaneous Lesions in Iranian Neonates and Their Relationships with Maternal-Neonatal Factors: A Prospective Cross-Sectional Study - Hossein Firouzi; Iman Jalalimehr; Zahra Ostadi; Siavash Rahimi (Dermatology Research and Practice)
Cutaneous lesions are common in the neonatal period and mostly physiological, transient, and self-limited; uncommonly, they are pathological and require treatment and cooperation between neonatologists and dermatologists. Particular conditions, like prematurity, can influence the onset, type, and evolution of cutaneous manifestations. Of the several articles in the literature about skin findings in newborns, only a few were performed in Iran. We aimed to investigate dermatological findings in a sample of neonates within the first three days of life and to evaluate the association between skin lesions and neonatal- or maternal-related variables. A total of 1202 newborns, hospitalized in the Department of Pediatrics of Imam Sajjad Hospital of Ramsar and Shahid Rajaee Hospital of Tonekabon, Iran, for two years, were examined. All skin findings were recorded, and information on neonatal and maternal variables was collected and analyzed to detect statistically significant associations. Skin lesions were present in 958 newborns (79.8%). The prevalence of milia, erythema toxicum, salmon patch, and Mongolian spots were 45.2%, 43%, 37.3%, and 37%, respectively. Natural vaginal delivery, use of medication, term gestation, and maternal disease were associated with a higher incidence of cutaneous lesions in neonates. Milia, erythema toxicum, Mongolian spots, and genital hyperpigmentation were seen more frequently in the male gender. Conversely, skin desquamation was seen more frequently in females. Among maternal diseases, gestational diabetes mellitus, urinary tract infection, preeclampsia, hypertension, psychiatric disorders, and uterine infection were associated with a higher prevalence of cutaneous lesions. Neonatal cutaneous lesions are a common source of concern in parents and inexperienced physicians. Therefore, prompt recognition of neonatal cutaneous lesions is essential in order to avoid unnecessary diagnostic and therapeutic procedures.